Enhancing structural stability of NaCrO2 by Nb-substituting for sodium-ion battery - Wang, Shuo; Chen, Fei; He, Hai-yan; Zhu, Yi-ran; Liu, Huai-bing; Chen, Chun-hua (Journal of alloys and compounds, 2022)
As an attractive cathode material, the layered sodium chromium oxide NaCrO2 (NCO) can provide a reversible capacity of around 120 mAh g−1 between 2.0 and 3.6 V, which corresponds to about 0.5 Na per formula is extracted/inserted. However, irreversible phase transition happens in NaxCrO2 when x is less than 0.4 and the potential is exceeding 3.6 V vs. Na+/Na. To improve its high-potential structural stability, Nb5+ is introduced to Cr3+ site by a sol-gel method successfully in this study. The influences of Nb5+ doping on the crystal structure and electrochemical properties are explored. As a result, a more stable structure as well as a higher ionic conductivity are achieved in Na0.94Cr0.97Nb0.03O2 (NCO-Nb3), exhibiting better rate performance and cycling stability between 2.0 and 3.6 V and 2.0–3.7 V. When elevating the charging cut-off voltage to 3.8 V, 4.0 V, 4.4 V, the initial coulombic efficiencies of NCO-Nb3 are still significantly higher than those of pristine NCO. •Pentavalent Nb5+ is substituted in Cr3+ site successfully, and the lattice spacing is enlarged.•The structure stability and ionic conductivity are improved with the doping of Nb5+.•Enhanced rate performances and stable cycle performances are achieved in different voltage ranges.•When tested between 2.0 and 3.7 V, NCO-Nb3 can achieve 1000 cycles at 10 C.